Metal‐ and Reagent‐Free Anodic C−C Cross‐Coupling of Phenols with Benzofurans leading to a Furan Metathesis. Issue 23 (25th March 2018) - Lips, Sebastian; Frontana‐Uribe, Bernardo Antonio; Dörr, Maurice; Schollmeyer, Dieter; Franke, Robert; Waldvogel, Siegfried R.
Abstract: Heterobiaryls consisting of a phenol and a benzofuran motif are of significant importance for pharmaceutical applications. An attractive sustainable, metal‐ and reagent‐free, electrosynthetic, and highly efficient method, that allows access to (2‐hydroxyphenyl)benzofurans is presented. Upon the electrochemical dehydrogenative C−C cross‐coupling reaction, a metathesis of the benzo moiety at the benzofuran occurs. This gives rise to a substitution pattern at the hydroxyphenyl moiety which would not be compatible by a direct coupling process. The single‐step protocol is easy to conduct in an undivided electrolysis cell, therefore scalable, and inherently safe. Abstract : Attaching and replacing within the benzofuran leads to an unexpected and so‐far unknown transformation and substitution pattern of heterobiaryls consisting of benzofurans and phenols. This electrochemical protocol exploits the HFIP directed dehydrogenative cross‐coupling in a reagent‐ and metal‐free manner, being inherently safe and scalable.